"ZIGZAG" PLANNING OF TOURIST ROUTES AS A TOOL FOR SPATIAL DEVELOPMENT AND SUSTAINABILITY OF TOURISM (USING THE EXAMPLE OF THE FERGHANA REGION) (Scientific journal of the Fergana State University, 2026)
The article is devoted to the development and implementation of "zigzag" routing of tourist routes in the Ferghana region as a tool for sustainable tourism development. The authors analyze the existing infrastructure of the region, as well as the cultural and historical potential for creating more flexible and rich tourist routes. The use of innovative approaches is being considered that will ensure an even distribution of tourist flows, the involvement of small territories and the preservation of cultural heritage. The article also provides a comparison with international experience and analyzes regulatory and legal support in Uzbekistan. The expected effect of the model's implementation includes not only the development of the tourism industry but also the socio-economic improvement of the region.